Zakaj poka jeklo pri kaljenju? - Legat, Franc (Kovine zlitine tehnologije, 1998)
The stresses in quenchings by heating and quenching of steels as well as the effect of different factors on cracking are explained.
Keywords: razpoke; jeklo; kaljenje; mikrostruktura